THE STRATEGY OF INDONESIAN MINISTRY OF TOURISM IN WONDERFUL INDONESIA’S BRANDING THROUGH SOCIAL MEDIA - Denny Prawibowo; Oktaviana Purnamasari (Perspektif Komunikasi: Jurnal Ilmu Komunikasi Politik dan Komunikasi Bisnis, 2019)
Currently,  the  rise  of  social  media  with  various  platforms  has  experienced  a  giant  leap.  The  high  demands  of information  accessed  quickly  by  the  community  through  social  media  becomes  a  certain  concern  for  the Indonesian  Ministry  of  Tourism  to  use  social  media  as  a  tool  in  promoting  and  building  Indonesian  tourism brands. Social media is also seen as having potential benefit to increase tourism sector and strengthen Wonderful Indonesia's branding quickly and precisely. This study aims to determine the strategy of the Ministry of Tourism on  Wonderful  Indonesia  branding  through  social  media,  find  out  the  types  of  social  media  used  and  identified Wonderful Indonesia's branding strategies related to planning and positioning, program design, performance and maintaining brand equity in the context of social media. The theory used in this study is Social Media theory and Strategic  Brand  Management  theory  by  Kevin  Keller,  including  identifying  and  developing  brand  plans, designing  and  implementing  brand  marketing  programs,  measuring  and  interpreting  brand  performance,  and growing  and  maintaining  brand  equity.  The  approach  used  in  this  study  is  qualitative  with  descriptive  method. For data collection techniques, we used depth interviews with key informan of the Ministry of Tourism, and key informan  of  social  media‟s  followers.  Observations  were  also  made  on  social  media  used  by  the  Ministry  of Tourism,  namely  Facebook,  Instagram,  Twitter,  Youtube  and  Googleplus.  Results  of  this  study  indicated  that tourism's strategy in Wonderful Indonesia's branding through social media was carried out in several stages; the first  stage  was  planning.  In  2015,  re-branding  was  conducted  with  the  addition  of  typography  and  touches  on Wonderful  Indonesia‟s  logo.  Then  the  second  stage  was  the  design  of  the  program  by  placing  the  right positioning for each Indonesian tourism destination which includes three elements of tourism products, namely natural,  cultural  and  man-made  with  marketing  strategy  programs  that  are  carried  out  namely  BAS  (Branding, Advertising and Selling) which refers in major cities of the world such as Berlin, New York, Amsterdam, Madrid and  Paris.  The  third  stage  was  the  performance  of  the  Ministry  of  Tourism,  which  according  to  the  Central Agency  Statistics,  foreign  tourist  arrivals  to  Indonesia  in  2017  increased  rapidly  to  14.4  million  tourists.  In addition, another proof of performance was Wonderful Indonesia's physical branding ranked 42nd in 2018 set by the  World  Economy  Forum.  The  fourth  stage  was  to  grow  and  maintain  brand  equity.  This  was  achieved  by Wonderful Indonesia by gaining 46 awards in 22 countries in 2016. Then in 2017 Wonderful Indonesia received 27 awards in 13 countries, whether in 2018 won "Brand of the Year Indonesia 2018" by Philip Kotler Center for ASEAN Marketing. Moreover, at the end of 2017, the growth number of foreign tourists was recorded at 22%. Keywords: Branding, Social Media, Tourism, Wonderful Indonesia.